Optical‐transparent Wi‐Fi bandpass mesh‐coated frequency selective surface. Issue 5 (1st February 2014) - Han, Y.; Liu, Y.M.; Jin, P.; Liu, B.; Ma, J.; Tan, J.B.
Abstract : To simultaneously achieve a high optical‐transparency and Wi‐Fi bandpass filtering characteristics for optical windows, a novel mesh‐coated frequency selective surface (FSS) is designed and fabricated using an ultraviolet lithography technique. Simulation and experimental results show that the resonant centre frequency of the proposed mesh‐coated FSS is about 5.3 GHz with a transmittance loss of −2 dB, while its optical transmittance is above 87.5% in the infrared (IR) waveband ranging from 1.35 to 3.3 μm. Moreover, such a FSS has the merits of ameliorable electromagnetic shielding effectiveness and improvable optical transmittance by optimising the thickness of the mesh layer. Both the design procedure and experimental measuring results are presented and discussed.